(untitled) (Applied Biological Research, 2014)
The present study was aimed to assess the hepatoprotective and anti oxidant potential of hydro-alcoholic root extract of ashwagandha (Withania somnifera) against liver dysfunction in geriatric canine. Geriatric canine (50) with hepatic dysfunction were divided randomly into 2 equal groups. The treatment group animals received principal therapy in combination with hydro-alcoholic root extract of W. somniferous for 28 consecutive days, while control group received only principal therapy as per the cause of disease which resulted in hepatic derangement. The herbal treatment of W. somnifera root extract significantly improved serum ALT, AST, albumin, cholesterol and protein levels. SOD, GSH, LPO and catalase levels regained to normal levels in treatment group animals in post-treatment period as compared to pre-treatment period. The results suggest that crude hydro-alcoholic root extract of W. somnifera possesses biologically active principles that are hepatoprotective and anti-oxidant in nature. It provides an opportunity of alternative therapy with medicinal plant for small animals that are not able to use the allopathic drugs.